A review on the mechanisms underlying the antitumor effects of natural products by targeting the endoplasmic reticulum stress apoptosis pathway - Zhang, Jie-Xiang; Yuan, Wei-Chen; Li, Cheng-Gang; Zhang, Hai-Yan; Han, Shu-Yan; Li, Xiao-Hong (Frontiers in Pharmacology, 2023)
Cancer poses a substantial risk to human life and well-being as a result of its elevated incidence and fatality rates. Endoplasmic reticulum stress (ERS) is an important pathway that regulates cellular homeostasis. When ERS is under- or overexpressed, it activates the protein kinase R (PKR)-like endoplasmic reticulum kinase (PERK)-, inositol-requiring enzyme 1 (IRE1)- and activating transcription Factor 6 (ATF6)-related apoptotic pathways to induce apoptosis. Tumor cells and microenvironment are susceptible to ERS, making the modulation of ERS a potential therapeutic approach for treating tumors. The use of natural products to treat tumors has substantially progressed, with various extracts demonstrating antitumor effects. Nevertheless, there are few reports on the effectiveness of natural products in inducing apoptosis by specifically targeting and regulating the ERS pathway. Further investigation and elaboration of its mechanism of action are still needed. This paper examines the antitumor mechanism of action by which natural products exert antitumor effects from the perspective of ERS regulation to provide a theoretical basis and new research directions for tumor therapy.